Nonrandom X-Chromosome Inactivation—an Artifact of Cell Selection - Mukherjee, Barid B. (1972)
The present study shows that a high degree of variability in the distribution of XX and XY cells exists among various tissues of artificially assembled or spontaneously occurring mouse chimeras. This variation from the expected equal distribution in various tissues of an animal may have resulted from random distribution, unequal segregation, or selective differences of such cells during development. This variation may also explain the observed intertissue and interanimal variations in the distribution of inactive paternal and maternal X-chromosomes in some mammalian females.